Explanation for the signs and symptoms of tooth eruption: mast cells - Franzolin, Solange De Oliveira Braga; Pardini, Maria Inês Moura Campos; Francischone, Leda A.; Deffune, Elenice; Consolaro, Alberto (Dental Press International, 2019)
Abstract This study contributes to the understanding of the mechanisms associated with signs and symptoms of tooth eruption, by investigating the presence of mast cells in pericoronal tissues during the intraosseous (Group 1) and submucosal (Group 2) phases of eruption. We compared findings for these two groups with each other and with those for the oral mucosa (Group 3). In each group, 14 specimens were analyzed microscopically after hematoxylin and eosin staining and immunohistochemical analysis of c-Kit and tryptase expression. Results revealed that the number and density of mast cells is different in follicular tissues according to the eruption phase, which may mean that: 1) masticatory trauma of the oral mucosa and dental follicles in the submucosa may explain why reduced enamel epithelium exposes enamel to the cells of the connective tissue; 2) exposure of antigenic enamel proteins might correspond to the release of sequestered antigens, which may lead to the interaction of IgE and a greater number of mast cells in the region; and 3) the consequent degranulation and the local release of mediators, such as histamine, leukotrienes, prostaglandins, proteases, cytokines and growth factors, contribute to the understanding of signs and symptoms associated with tooth eruption.

Resumo Para contribuir com a compreensão dos mecanismos relacionados à sintomatologia e aos sinais associados à erupção dentária, investigou-se a presença de mastócitos nos tecidos pericoronários na fase intraóssea (Grupo 1) e submucosa (Grupo 2), comparando-os entre si e com a mucosa bucal (Grupo 3). Em cada grupo, 14 espécimes foram analisados microscopicamente em cortes corados com hematoxilina e eosina, e imunocitoquimicamente marcados com Ckit e Triptase. Pelos resultados obtidos, concluiu-se que a quantidade/densidade dos mastócitos é diferente nos tecidos foliculares de acordo com a fase de erupção, o que permite inferir que: 1) O traumatismo decorrente da mastigação sobre o conjunto “mucosa bucal com o folículo pericoronário na submucosa” pode explicar porque o epitélio reduzido exporia o esmalte às células do tecido conjuntivo; 2) A exposição das proteínas do esmalte com propriedades antigênicas corresponderia à liberação de antígenos sequestrados que levariam à interação de IgE e mastócitos em número aumentado na região; e 3) A consequente degranulação e liberação de mediadores no local, como histamina, leucotrienes, prostaglandinas, proteases, citocinas e fatores de crescimento, contribuem para a compreensão dos sinais e sintomatologia atribuídos à erupção dentária.
Keywords: Tooth eruption; Dental follicle; Mast cells; Odontogenesis; Erupção dentária; Folículo pericoronário; Mastócitos; Odontogênese